Climate Change and Plant Abiotic Stress Tolerance 2013
DOI: 10.1002/9783527675265.ch09
|View full text |Cite
|
Sign up to set email alerts
|

Drought Stress Responses in Plants, Oxidative Stress, and Antioxidant Defense

Abstract: Global climate change is currently viewed as the most devastating threat to the environment, and is now gaining considerable attention from farmers, researchers, and policy makers because of its major influence on agriculture. The situation is becoming more serious due to gradual increases in the complex nature of the environment, and due to the unpredictability of environmental conditions and global climate change. One of the most acute environmental stresses presently affecting agriculture is drought, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
95
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(109 citation statements)
references
References 207 publications
(231 reference statements)
2
95
0
2
Order By: Relevance
“…It was reported that the physiological processes influenced by drought can be identified by the biochemical characterization of plant tissues under stress conditions [46]. Limited research was conducted to characterize the biochemical compounds such as protein, amino acids, carbohydrates, and phenolics in the breeding program as a tool for selection, but this tool has promise in selecting for abiotic stress tolerance [24,47]. The changes of δ …”
Section: Soybean -The Basis Of Yield Biomass and Productivity 146mentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the physiological processes influenced by drought can be identified by the biochemical characterization of plant tissues under stress conditions [46]. Limited research was conducted to characterize the biochemical compounds such as protein, amino acids, carbohydrates, and phenolics in the breeding program as a tool for selection, but this tool has promise in selecting for abiotic stress tolerance [24,47]. The changes of δ …”
Section: Soybean -The Basis Of Yield Biomass and Productivity 146mentioning
confidence: 99%
“…Therefore, these biochemical compounds are important to understand the relationship between drought stress and drought tolerance and for decision-making when breeding for drought tolerance [23]. Since drought stress results in limiting the growth and development of the plant and consequently the supply of the photosynthate to grain during grain filling [24], the chemical composition of the grain and its quality can be affected by drought stress [12,25]. The effect of drought on seed quality could be due to the decrease of total soluble sugars especially in the grain under drought stress due to decreases in the levels of sucrose, stachyose, and verbascose.…”
Section: Introductionmentioning
confidence: 99%
“…Drought also represents an oxidative stress to plants by enhancing the accumulation of reactive oxygen species (ROS) in cells, including superoxide radicals (O 2 . − ), hydrogen peroxide (H 2 O 2 ), and hydroxyl radicals (OH − ) [4]. These ROS can oxidize or peroxidize lipids, proteins, enzymes, pigments, and DNA, thereby further damaging the structure and function of cells, and ultimately inducing cell death [5].…”
Section: Introductionmentioning
confidence: 99%
“…To alleviate oxidative stress caused by drought, an efficient antioxidant mechanism involving nonenzymatic and enzymatic systems has evolved [7]. The former includes flavonoids, alkaloids, and phenols, whereas the enzymatic antioxidant system involves a series of enzymes, including superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT) [4,5]. Antioxidant systems in various plant species have been studied, and antioxidant enzymes that effectively protect plants against oxidative damage induced by various biotic and abiotic stresses, including drought, have been found [4,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation